Unveiling Communication Quality in the Construction Industry: A Multilevel Evaluation of Project, Group, and Individual Outcomes - Kunkcu, Handan; Koc, Kerim; Gurgun, Asli Pelin (ASCE-AMER SOC CIVIL ENGINEERS, 2026)
Confronted with the multifaceted risks associated with the construction industry, communication quality is considered as an indispensable need for improving project success. Past research on communication in construction has made significant progress; however, existing literature lacks a multilevel framework that captures factors influencing construction employees' communication quality across a three-level-hierarchy: (1) project level (top), (2) group level (medium), and (3) individual level (bottom). The present study addresses this gap by developing a conceptual model showing the effects of operational hierarchic levels (i.e., project, group, and individual levels) on communication quality, as well as including project complexity as a moderating variable. Using the data collected from 447 construction professionals, structural equation modeling (SEM) analysis uncovers the role of exploring different perspectives at project level and shared vision at individual level in maintaining high-quality communication among project teams. The results of the moderation analysis reveal that project complexity has an interaction effect with team diversity and shared vision, which also influences communication quality. This study provides valuable insights into communication in construction, aiding practitioners to improve their communication performance and develop effective communication strategies. The findings contribute to the understanding of significant contextual and individual factors by proposing a model that detects project's process of reflection and exploration (project level), practitioners' varying cultural and professional backgrounds (group level), and their personal innovative and collective acts (individual level), underpinning their importance in ensuring the quality of communication.
Keywords: Communication; Knowledge transfer; Team diversity; Project complexity; Structural equation modeling; Construction projects; COMPLEXITY; PERFORMANCE; MANAGEMENT; LEADERSHIP; SUCCESS; SYSTEMS; IMPACT; MODEL; TRUST; Construction & Building Technology; Engineering